The General Psychiatric Syndrome as a Transdiagnostic Hypothesis: A Critical Appraisal of Evidence, Interpretation and Clinical Reach - Luiz Costa; Fernando Martins Castanheira Júnior; Giovanna Azevedo Rodrigues; Marcelo Caixeta (International Neuropsychiatric Disease Journal, 2026)
Persistent comorbidity, diagnostic instability and the scarcity of disorder-specific causes have encouraged the proposal that a single superordinate dimension underlies liability to all common mental disorders. This proposition, expressed empirically as the general factor of psychopathology and framed conceptually as a general psychiatric syndrome, now shapes nosological reform, aetiological research and the design of youth mental health services. Its status remains contested. This critical narrative review evaluates the hypothesis across five domains of evidence: psychometric modelling, quantitative and molecular genetics, structural neuroimaging and neurocognition, developmental epidemiology, and clinical translation. Literature published between January 1999 and June 2026 was identified through structured searching of biomedical and multidisciplinary scholarly sources, supplemented by citation tracking of recent reviews and of a 2026 target-article exchange devoted to the topic. Sources were appraised for design adequacy, sample independence, replication, and the correspondence between statistical models and the substantive claims drawn from them. Evidence for a strong and replicable general dimension at the phenotypic level is robust. It accounts for the majority of reliable symptom variance from early childhood to adulthood, aggregates within families, and predicts impairment more consistently than narrower factors. Evidence bearing on its interpretation is considerably weaker. Competing accounts framing the dimension as negative emotionality, disinhibition, thought dysfunction, low cognitive ability or an index of impairment are only partially separable empirically, and several are close to statistically equivalent. Molecular genomic analyses supply the strongest disconfirming signal, repeatedly favouring several correlated genomic factors over a single dimension of genetic risk. Neuroimaging associations are modest, derive from a small number of overlapping cohorts, and have not produced diagnostic or prognostic utility. Transdiagnostic psychological treatments perform comparably to disorder-specific protocols, although this parity does not establish a shared causal mechanism. The general dimension is best regarded at present as a well-replicated descriptive summary of liability and impairment rather than a demonstrated syndrome with unitary aetiology. Clinical adoption should follow evidence of incremental decision-making value, which has not yet been generated.